Concurrent pulmonary infection and perinephric abscess: a case report and literature review - Guo, Lixin; Ma, Li; Ren, Wenjing; Tang, Xiaoli; Hao, Yuqiu; Gao, Peng (Frontiers in Immunology, 2025)
This report details the case of a 64-year-old male with well-controlled type 2 diabetes mellitus and hypertension. The patient presented with a 20-day history of progressive dyspnea, cough, and intermittent fever, which worsened despite antibiotic treatment. The initial assessment revealed leukocytosis, neutrophilia, and abnormal chest computed tomography (CT) findings, which led to a provisional diagnosis of pulmonary infection. However, empirical antibacterial therapy was ineffective. Further investigations revealed a right perinephric abscess and empyema caused by an oral anaerobic bacterial infection. Although the sputum cultures were negative, targeted next-generation sequencing (tNGS) identified multiple oral anaerobes. The patient was treated with metronidazole and drainage. After 33 days, the symptoms and laboratory abnormalities gradually resolved. Follow-up over one year demonstrated complete resolution of symptoms, normalization of inflammatory markers and no recurrence of the infection. This case highlights the importance of considering occult anaerobic infections in refractory febrile patients with diabetes, while also raising awareness of the rare complication of perinephric abscess and highlighting the value of tNGS in pathogen identification.